2012
DOI: 10.1073/pnas.1113740109
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of local knowledge to the physical limnology of Lake Como, Italy

Abstract: This article shows how local knowledge may be valuably integrated into a scientific approach in the study of large and complex hydrological systems where data collection at high resolution is a challenge. This claim is supported through a study of the hydrodynamics of a large lake where qualitative data collected from professional fishers was combined with theory to develop a hypothesis that was then verified by numerical modeling. First the fishermen's narratives were found to describe with accuracy internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Integration of social and natural science methodologies has gained traction over the past decade, with an increased recognition that LEK and scientific knowledge can be complementary, together providing increased confidence in ecological information when there is agreement between the methods (Huntington et al 2004, Thornton andScheer 2012). Indeed, a growing number of case studies show concordance and corroboration between LEK and standard scientific data, including measurements of animal abundance and distribution (Anadon et al 2009, 2010, Azzurro et al 2011) and physical features of lake habitats (Laborde et al 2012). Quantifying variance in ecological data is standard practice in scientific surveys, yet assessment of variance in ecological information provided by resource users has received relatively little attention (Huntington et al 2004, but see Ainsworth 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Integration of social and natural science methodologies has gained traction over the past decade, with an increased recognition that LEK and scientific knowledge can be complementary, together providing increased confidence in ecological information when there is agreement between the methods (Huntington et al 2004, Thornton andScheer 2012). Indeed, a growing number of case studies show concordance and corroboration between LEK and standard scientific data, including measurements of animal abundance and distribution (Anadon et al 2009, 2010, Azzurro et al 2011) and physical features of lake habitats (Laborde et al 2012). Quantifying variance in ecological data is standard practice in scientific surveys, yet assessment of variance in ecological information provided by resource users has received relatively little attention (Huntington et al 2004, but see Ainsworth 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fishers' LEK does not always agree with biological surveys (Aswani and Hamilton 2004, Silvano and Begossi 2010, ), and fishers have been shown to possess limited knowledge on certain topics in some cases, such as regarding the spawning seasons and habitats of some fishes (Silvano et al 2006). Nevertheless, recent surveys based on structured and systematic research have demonstrated that fishers' LEK may be highly compatible with biological, fisheries, and even physical data (Silvano and Begossi 2005, , , Laborde et al 2012), therefore representing a useful, but often neglected, data source for fisheries management. Indeed, in some situations, fishers' LEK may be a unique available source of data, such as regarding fish migrations in large rivers (Valbo‐Jorgensen and Poulsen 2000) or along the coast (Silvano et al 2006), fish nursery sites (), and past abundance trends of exploited fish and invertebrates (Saenz‐Arroyo et al 2005, Salomon et al 2007, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its application in improving knowledge about specific organisms, the LEK of resource users can also be helpful for evaluating broader environmental changes over temporal scales ranging from years to decades. For example, LEK has been useful for evaluating the temporal patterns of fish abundance and associated ecosystem processes in the North Atlantic (Rochet et al 2008), changes in the vegetation composition and productivity of grazing fields (Fernandez-Gimenez 2000), fish kills linked to the hydrological cycle in a tropical wetland (Calheiros et al 2000), the hydrodynamics of an alpine lake (Laborde et al 2012) and the long-term impacts of changes in climatic conditions and ice cover for Arctic animals (Huntington 2011). However, although the potential of LEK is currently recognized, few studies have compared LEK and biological data from the same region and at the same spatial scale (Aswani and Hamilton 2004, Salomon et al 2007, Jones et al 2008, Rochet et al 2008, Silvano and Begossi 2010, Daw et al 2011, few of these comparative surveys have been conducted in freshwater ecosystems .…”
Section: Introductionmentioning
confidence: 99%
“…The erosion of Tibetans' LEK, without replacement by the production of new knowledge suited to new circumstances, could reduce local capacity to cope with environmental changes and have cascading effects for ecosystem health and the provision of ecosystem services. Loss of LEK also represents a missed opportunity for pastoralists' knowledge to inform and improve regional climate adaptation policies and western scientific understandings of the ways in which this remote system is being affected by global change (Homann et al 2008, Reid et al 2009, Chaudhary and Bawa 2011, Fu et al 2012, Laborde et al 2012, Oba 2012, Smith and Sharp 2012). …”
Section: Introductionmentioning
confidence: 99%